Exotic Trees and Shrubs of Kashmir - Singh, Gurcharan; Kachroo, P. (Indian Forester, 1983)
The present paper discusses the exotic trees and shrubs of Kashmir which include about 90 per cent of woody elements grown in the valley. The exotics of Kashmir have their native homes in three principal regions: Sino-Japanese region, Mediterranean region and N. American region, contributing 38, 45 and 12 per cent of our exotics respectively. 118 exotic woody taxa are listed. Relevant taxonomic and ecological data are presented for each.